Original article Reexcision and perioperative high-dose-rate brachytherapy in the treatment of local relapse after breast conservation: an alternative to salvage mastectomy - Polgár, Csaba; Sulyok, Zoltán; Major, Tibor; Fröhlich, Georgina; Takácsi-Nagy, Zoltán; Fodor, János (Journal of Contemporary Brachytherapy, 2009)
Purpose: To evaluate the feasibility and efficacy of second breast-conserving surgery with reirradiation using perioperative high-dose-rate interstitial brachytherapy for the treatment of local recurrence developing after previous breast-conserving therapy. Material and methods: Between 1999 and 2007, twelve patients with isolated local recurrence initially treated for breast carcinoma with the use of conservative surgery and radiation therapy, underwent a repeat breast-conserving surgery and perioperative high-dose-rate multicatheter brachytherapy. Breast cancer related events, late side effects, and cosmetic results were assessed retrospectively. Results: At a median follow-up of 56 months (range: 8-112) second local recurrence has not occurred, yielding a 100% mastectomy-free survival. Four patients (33.3%) developed subsequent distant metastasis and died of breast cancer. The 5-year actuarial rate of disease-free, cancer-specific, and overall survival was 65.6%, 78.6%, and 78.6%, respectively. Cosmetic results were rated good, fair, poor and unknown in 6 (50%), 2 (17%), 1 (8%) and 3 (25%) patients, respectively. Grade 2 skin toxicity and fibrosis occurred in 1 (8%) and 2 (17%) patients. Asymptomatic fat necrosis was detected in 6 (50%) women. No patient developed grade 3-4 late side effects. Conclusions: Second breast-conserving surgery followed by partial breast reirradiation is a safe and effective option for the management of selected patients developing local recurrence after previous breast-conserving therapy. Perioperative high-dose-rate brachytherapy with adequate fractionation may decrease the risk of second local relapse with acceptable cosmetic results and low rate of late side effects.